PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN SISTEM AGRIBISNIS KUBIS - Siska Prihantiwi; Totok Mardikanto; Agung Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2016)
This research aims to determine the causes of the role of educator, cabbage agribusiness system development, the role of educator, relationship roles extension with cabbage agribusiness development in Tawangmangu District, Karanganyar Regency.  This research  used  a  quantitative  approach. The  research  location was selected  Tawangmangu  District,  which  has  the  highest production of cabbage  in Karanganyar Regency. The data was used primary and secondary. Data analysis method was used partial correlation. The results of research showed agribusiness system development phase cabbage cultivation availability of production facilities and  the  very  high  criteria,  harvest  and  post-harvest  and  marketing  in  the  high criteria, institutional support in the low criteria. The role of agricultural extension as a motivator, mediator, supervisor and facilitator are in high criteria. The causes of extension role who are in the high criteria were the age and income of farmers, to the level of agricultural education and training in low criteria. Between roles as a motivator with a marketing instructor showed a significant relationship. Instructor's role as a mediator between the institutional supports showed a significant relationship. Between the role of agricultural extension as a supervisor and facilitator with cabbage agribusiness system development showed no significant relationship. Between the ages of farmers and role of instructor showed a significant relationship. The  relationship  between  level  of  education,  income  and  agricultural  training, showed no significant association.